Understanding university brand loyalty: the mediating role of attitudes towards the department and university - (:unkn) unknown (ELSEVIER SCIENCE BV, 2016)
For today's competitive academic environment, brand management in higher education is becoming highly important. As students have many options available to them, there is a growing need to study factors that enable higher education institutions to attract and retain students. In literature, there are many factors that foster or challenge branding activities of universities. In this study, the mediating role of attitude on university performance variables and university brand loyalty relationship is investigated. A survey is used as a research instrument and applied to university students. Data is collected from 321 university students studying at business administration department of a public university. Hierarchical multiple regression is used to test the hypotheses which revealed partial mediation of attitude between the relationship of university performance and university brand loyalty. (C) 2016 The Authors. Published by Elsevier Ltd.
Keywords: University brand; Brand loyalty; Brand attitude; University performance; BEHAVIOR; MODEL